COVID‐19 and acute pancreatitis: A systematic review - Oyedotun Ikechukwu Babajide; Ekwevugbe Ochuko Ogbon; Anuoluwapo Adelodun; Olufunso Agbalajobi; Yetunde Ogunsesan (JGH Open, 2022)
Abstract We aimed to systematically review the relationship between severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and acute pancreatitis (AP). The global pandemic of coronavirus disease 2019 (COVID‐19) caused by SARS‐CoV‐2 infection causes respiratory symptoms and notably also affects the gastrointestinal (GI) system. A systematic review of the available literature on the topic was performed with a search key using the terms “SARS COV 2,” “Pancreatitis,” “COVID‐19” and synonyms. The search was conducted on 27 December 2020 using PubMed, EMBASE, CENTRAL, Web of Science, and Scopus. A meta‐analysis was not conducted due to the low quality and poor comparability of the studies. We reviewed 66 studies that reported data on patients with polymerase chain reaction‐confirmed SARS‐CoV‐2 infection and AP using the Atlanta Criteria. Our evaluation revealed a wide age range and diverse clinical presentation of COVID‐19 with or without symptoms of AP, some of which preceded typical COVID‐19 symptoms. We observed a myriad of complications and one study revealed that patients with both conditions were more likely to require mechanical ventilation and had longer lengths of hospital stay compared with patients with AP without COVID‐19. Treatment for AP was mostly supportive, with varied therapies employed for COVID‐19. Most cases were considered idiopathic and presumed to be SARS‐CoV‐2‐induced as established etiological factors were not reported. AP should be considered in COVID‐19 patients, especially in those exhibiting GI symptoms. Evidence to establish a causal relationship between SARS‐CoV‐2 infection and AP is currently lacking.